Third Report of the Committee on Photochemistry: Reprint and Circular Series of the National Research Council (The National Academies Press, 1938)
Keywords: Math, Chemistry, and Physics

Climate and Health Challenges Posed by Black Carbon: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In October 2012, the National Academies of Sciences, Engineering, and Medicine and the Russian Academy of Sciences held a workshop in Moscow, Russia, on the Challenges of Black Carbon (BC). The workshop was carried out pursuant to the long-standing bilateral NAS-RAS Agreement on Cooperation in the Fields of Science, Engineering, and Medicine and attracted considerable interest among scientists and policy experts. More than 50 Russian and American scientists and specialists participated. The participants addressed many areas of scientific interest regarding BC dispersal, particularly in the northern latitudes, and called for continued cooperation between the academies on BC-related issues. A second workshop was held in April 2016 and included 29 technical presentations from individuals at 11 Russian and 8 U.S. institutions. The primary goals of the workshop were to learn about current research on BC and to identify opportunities for scientific and technical collaboration among experts in the United States and Russia.
Keywords: Earth Sciences; Health and Medicine

A Plan for a Research Program on Aerosol Radiative Forcing and Climate Change - National Research Council (The National Academies Press, 1996)
This book recommends the initiation of an "integrated" research program to study the role of aerosols in the predicted global climate change. Current understanding suggest that, even now, aerosols, primarily from anthropogenic sources, may be reducing the rate of warming caused by greenhouse gas emissions. In addition to specific research recommendations, this book forcefully argues for two kinds of research program integration: integration of the individual laboratory, field, and theoretical research activities and an integrated management structure that involves all of the concerned federal agencies.
Keywords: Environment and Environmental Studies; Earth Sciences

Potential Applications of Concentrated Solar Energy: Proceedings of a Workshop - National Research Council (The National Academies Press, 1991)
This book assesses the current state of the field in a number of potential applications and discusses technologies for which concentrated solar energy might be utilized. It contains all the papers submitted by the speakers as well as summaries of the presentations and discussions that followed each session.
Keywords: Energy and Energy Conservation

Protecting Visibility in National Parks and Wilderness Areas - National Research Council (The National Academies Press, 1993)
Scenic vistas in most U.S. parklands are diminished by haze that reduces contrast, washes out colors, and renders distant landscape features indistinct or invisible. Protecting Visibility in National Parks and Wilderness Areas describes the current understanding of the nature and extent of haze in various regions of the United States. The book addresses the scientific and legal framework of efforts to protect and improve visibility, as well as methods for assessing the relative importance of anthropogenic emission sources that contribute to haze in national parks and for considering various alternative source control measures. The volume provides guidance on how to make progress toward the national goal of correcting and preventing visibility impairment due to human activities affecting large national parks and wilderness areas.
Keywords: Environment and Environmental Studies

Counterfeit Deterrent Features for the Next-Generation Currency Design - National Research Council (The National Academies Press, 1993)
Traditionally, counterfeit deterrent features restricted counterfeiting to only the dedicated craftsman. With the advent of highly sophisticated reprographic systems, this is no longer true. Redesign of U.S. banknotes is necessary in order to incorporate additional features aimed at discouraging counterfeiting using advanced copiers-scanners-printers. This volume evaluates a large number of such features while recommending a comprehensive national strategy for anticipating and responding to counterfeiting threats.
Keywords: Engineering and Technology

Advances in Photoreception: Proceedings of a Symposium on Frontiers of Visual Science - National Research Council (The National Academies Press, 1990)
One of a continuing series on Frontiers of Visual Science, this short volume contains papers presented at a recent symposium. These papers describe techniques for assessing the structure and function of photoreception, both in isolation and in aggregation as the "receptor mosaic" of the retina. Also described are dynamic and spatial sampling properties of photoreceptors, with an emphasis on techniques of measurement and associated models of retinal function. This volume should be of interest to basic vision scientists, clinical ophthalmologists, workers in human factors, and computer scientists curious about the visual apparatus of biological systems.
Keywords: Health and Medicine

Haze in the Grand Canyon: An Evaluation of the Winter Haze Intensive Tracer Experiment - National Research Council (The National Academies Press, 1990)
This book presents working principles for assessing the relative importance of anthropogenic emission sources that contribute to haze in U.S. national parks and wilderness areas and discusses various alternative source control methods. Haze in the Grand Canyon evaluates and recommends strategies for improving critical scientific and technical gaps in the information and databases on haze. It examines such topics as methods for determining individual source contributions, regional and seasonal factors that affect haze, strategies for improving air quality models, the interactive role of photochemical exodants, and scientific and technological considerations in choosing emission control measures.
Keywords: Environment and Environmental Studies

An Assessment of Four Divisions of the Physical Measurement Laboratory at the National Institute of Standards and Technology: Fiscal Year 2018 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
An Assessment of Four Divisions of the Physical Measurement Laboratory at the National Institute of Standards and Technology: Fiscal Year 2018 assesses the scientific and technical work performed by four divisions of the National Institute of Standards and Technology (NIST) Physical Measurement Laboratory. This publication reviews technical reports and technical program descriptions prepared by NIST staff and summarizes the findings of the authoring panel.
Keywords: Engineering and Technology

Opportunities in Chemistry: Today and Tomorrow - George C. Pimentel; Janice A. Coonrod (The National Academies Press, 1987)
Experts agree that the nation would benefit if more young people "turned on" to the sciences. This book is designed as a tool to do just that. It is based on Opportunities in Chemistry, a National Research Council publication that incorporated the contributions of 350 researchers working at the frontiers of the field. Chemistry educators Janice A. Coonrod and the late George C. Pimentel revised the material to capture the interest of today's student. A broad and highly readable survey, the volume explores: The role of chemistry in attacking major problems in environmental quality, food production, energy, health, and other important areas. Opportunities at the leading edge of chemistry, in controlling basic chemical reactions and working at the molecular level. Working with lasers, molecular beams, and other sophisticated measurement techniques and tools available to chemistry researchers. The book concludes with a discussion of chemistry's role in society's risk-benefit decisions and a review of career and educational opportunities.
Keywords: Math, Chemistry, and Physics

Mars Sample Return: Issues and Recommendations - National Research Council (The National Academies Press, 1997)
The Space Studies Board of the National Research Council (NRC) serves as the primary adviser to the National Aeronautics and Space Administration (NASA) on planetary protection policy, the purpose of which is to preserve conditions for future biological and organic exploration of planets and other solar system objects and to protect Earth and its biosphere from potential extraterrestrial sources of contamination. In October 1995 the NRC received a letter from NASA requesting that the Space Studies Board examine and provide advice on planetary protection issues related to possible sample-return missions to near-Earth solar system bodies.
Keywords: Space and Aeronautics

Interim Review of the Subsonic Assessment Project: Management, Science, and Goals - National Research Council (The National Academies Press, 1997)
Keywords: Earth Sciences; Space and Aeronautics

Measuring PM Emissions from Aircraft Auxiliary Power Units, Tires, and Brakes - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s Airport Cooperative Research Program (ACRP) Report 97: Measuring PM Emissions from Aircraft Auxiliary Power Units, Tires, and Brakes presents the results of a comprehensive test program designed to measure particulate matter (PM) emissions from auxiliary power units and from tires and brakes during the landing phase of operations of in-service commercial aircraft.The research results are designed to provide a significant contribution to the characterization of emissions from these sources with the goal of helping airports improve the accuracy of their PM emissions inventories.
Keywords: Transportation and Infrastructure

Potential Applications of Concentrated Solar Photons - National Research Council (The National Academies Press, 1991)
This book reviews current work and assesses the state of the art in potential applications of concentrated solar energy in nonelectric areas, such as water and waste treatment, photochemical processes, and materials processing. It identifies and recommends research needed for further development of promising applications.
Keywords: Energy and Energy Conservation

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2005 Symposium - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2006)
This volume includes 16 papers from the National Academy of Engineering's 2005 U.S. Frontiers of Engineering (USFOE) Symposium held in September 2005. USFOE meetings bring together 100 outstanding engineers (ages 30 to 45) to exchange information about leading-edge technologies in a range of engineering fields. The 2005 symposium covered four topic areas: ID and verification technologies, engineering for developing communities, engineering complex systems, and energy resources for the future. A paper by dinner speaker Dr. Shirley Ann Jackson, president of Rensselaer Polytechnic Institute, is also included. The papers describe leading-edge research on face and human activity recognition, challenges in implementing appropriate technology projects in developing countries, complex networks, engineering bacteria for drug production, organic-based solar cells, and current status and future challenges in fuel cells, among other topics. Appendixes include information about contributors, the symposium program, and a list of meeting participants. This is the eleventh volume in the USFOE series.
Keywords: Engineering and Technology; Space and Aeronautics

National Security and Homeland Defense: Challenges for the Chemical Sciences in the 21st Century - National Research Council (The National Academies Press, 2002)
This is the first report of seven in the Challenges for the Chemical Sciences in the 21st Century series. The report is based on discussions and presentations at a workshop, and is intended to help scientists and funding agencies set short- and long-term research agendas. It focuses on the challenges for chemists and chemical engineers with respect to threat reduction, preparation, situational awareness, and threat neutralization and remediation
Keywords: Conflict and Security Issues

Disposal of Industrial and Domestic Wastes: Land and Sea Alternatives - National Research Council (The National Academies Press, 1984)
Can decision makers meaningfully compare land versus sea options for waste disposal? Using available scientific data on waste behavior and new studies from East and West Coast dump sites, this book shows how to use a matrix approach to rank the ecological and health consequences of any combination of waste, site, and disposal system design.
Keywords: Environment and Environmental Studies

Fire Research Abstracts and Reviews, Volume 11 - National Research Council (The National Academies Press, 1969)
Keywords: Engineering and Technology

Bringing Public Health into Urban Revitalization: Workshop in Brief - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
On November 10, 2014, the Roundtable on Environmental Health Sciences, Research, and Medicine held a 1-day workshop titled "Bringing Public Health into Urban Revitalization." The purpose of the workshop was to explore public health issues related to the redesign of major U.S. cities, focusing on recent examples from Detroit, Michigan; New York City; and Washington, DC. Workshop speakers showed how rebuilding efforts provide an opportunity to reimagine the built environment, increase a sense of community, increase the role of public health departments and health systems, and increase the use of green technologies.
Keywords: Health and Medicine

The Atmospheric Effects of Stratospheric Aircraft Project: An Interim Review of Science and Progress - National Research Council (The National Academies Press, 1998)
Scientists and policy-makers alike are concerned that operation of a fleet of high-speed civil transport (HSCT) aircraft could significantly affect the global atmosphere. HSCT emissions may have a direct effect on the chemistry of the atmosphere, leading to changes in the distribution of ozone; they may also have indirect effects on ozone and on global climate through coupling with radiative and dynamical processes in the atmosphere. An assessment of the atmospheric impact of a fleet of HSCTs thus requires not only an understanding of the chemistry of the natural stratosphere and its possible perturbations by HSCT emissions, but also an understanding of the pathways for transport of HSCT emissions within the atmosphere, and the resulting temporal and spatial distribution of HSCT emissions. The results of NASA's Atmospheric Effects of Stratospheric Aircraft (AESA) project were summarized in a 1995 NASA assessment. The present report looks at that summary and at more recent work to evaluate the state of the science. AESA has made good progress in the past few years. Satellite and aircraft observations have elucidated important aspects of large-scale transport processes. Field campaigns have provided a much better picture of the relative importance, below 20 km altitude, of the major catalytic cycles for ozone destruction. Careful intercomparisons of assessment models have led to reduction of some of the differences among the models. However, a number of uncertainties and inconsistencies still remain.
Keywords: Space and Aeronautics

Lasers and Their Uses - National Research Council (The National Academies Press, 1983)
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

Bio-Inspired Signature Management for the U.S. Army: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The National Academies of Sciences, Engineering, and Medicine convened a workshop of subject-matter experts on September 16, 2019, to gather information that will improve understanding of the science and technology (S&T) issues and opportunities in signature management for future U.S. Army missions. This workshop was part of a series of S&T activities under the National Academies Board on Army Research and Development. The goals of this meeting were to identify clear paths that illuminate knowledge of how biological systems sense prey and mask their signatures; explore promising S&T avenues to pursue and ways to improve information sharing; and to encourage a community of scholars to pursue these ideas further. This publication highlights the presentations of the workshop.
Keywords: Conflict and Security Issues

Evaluating Air-Entraining Admixtures for Highway Concrete - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2007)
TRB's National Cooperative Highway Research Program (NCHRP) Report 578: Evaluating Air-Entraining Admixtures for Highway Concrete explores a procedure for evaluating air-entraining admixtures used in highway concrete. The procedure involves the testing of non-air-entrained concrete and concrete containing the air-entraining admixture under simulated field conditions. The appendixes to the report have been published as NCHRP Web-Only Document 101.
Keywords: Transportation and Infrastructure

Plasmas and Fluids - National Research Council (The National Academies Press, 1986)
Keywords: Math, Chemistry, and Physics; Space and Aeronautics

Biographical Memoirs: Volume 74 - National Academy of Sciences (The National Academies Press, 1998)
Biographic Memoirs: Volume 74 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography; Biology and Life Sciences

Urbanization, Energy, and Air Pollution in China: The Challenges Ahead: Proceedings of a Symposium - National Research Council; National Academy of Engineering (The National Academies Press, 2004)
In October 2003, a group of experts met in Beijing under the auspices of the Chinese Academy of Sciences, Chinese Academy of Engineering, and National Academy of Engineering (NAE)/National Research Council (NRC) of the National Academies to continue a dialogue and eventually chart a rational course of energy use in China. This collection of papers is intended to introduce the reader to the complicated problems of urban air pollution and energy choices in China.
Keywords: Energy and Energy Conservation; Environment and Environmental Studies

Shipboard Pollution Control: U.S. Navy Compliance with MARPOL Annex V - National Research Council (The National Academies Press, 1996)
Keywords: Environment and Environmental Studies; Earth Sciences

Assessment of Solid-State Lighting, Phase Two - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The standard incandescent light bulb, which still works mainly as Thomas Edison invented it, converts more than 90% of the consumed electricity into heat. Given the availability of newer lighting technologies that convert a greater percentage of electricity into useful light, there is potential to decrease the amount of energy used for lighting in both commercial and residential applications. Although technologies such as compact fluorescent lamps (CFLs) have emerged in the past few decades and will help achieve the goal of increased energy efficiency, solid-state lighting (SSL) stands to play a large role in dramatically decreasing U.S. energy consumption for lighting. Since the publication of the 2013 National Research Council report Assessment of Advanced Solid-State Lighting, the penetration of SSL has increased dramatically, with a resulting savings in energy and costs that were foreshadowed by that study. What was not anticipated then is the dramatic dislocation and restructuring of the SSL marketplace, as cost reductions for light-emitting diode (LED) components reduced profitability for LED manufacturers. At the same time, there has been the emergence of new applications for SSL, which have the potential to create new markets and commercial opportunities for the SSL industry. Assessment of Solid-State Lighting, Phase Two discusses these aspects of change—highlighting the progress of commercialization and acceptance of SSL and reviewing the technical advances and challenges in achieving higher efficacy for LEDs and organic light-emitting diodes. This report will also discuss the recent trends in SSL manufacturing and opportunities for new applications and describe the role played by the Department of Energy (DOE) Lighting Program in the development of SSL.
Keywords: Energy and Energy Conservation

Laser Eye Effects - H. G. Sperling (The National Academies Press, 1968)
Keywords: Biology and Life Sciences

Atomic, Molecular, and Optical Physics - National Research Council (The National Academies Press, 1986)
The goals of atomic, molecular, and optical physics (AMO physics) are to elucidate the fundamental laws of physics, to understand the structure of matter and how matter evolves at the atomic and molecular levels, to understand light in all its manifestations, and to create new techniques and devices. AMO physics provides theoretical and experimental methods and essential data to neighboring areas of science such as chemistry, astrophysics, condensed-matter physics, plasma physics, surface science, biology, and medicine. It contributes to the national security system and to the nation's programs in fusion, directed energy, and materials research. Lasers and advanced technologies such as optical processing and laser isotope separation have been made possible by discoveries in AMO physics, and the research underlies new industries such as fiber-optics communications and laser-assisted manufacturing. These developments are expected to help the nation to maintain its industrial competitiveness and its military strength in the years to come. This report describes the field, characterizes recent advances, and identifies current frontiers of research.
Keywords: Math, Chemistry, and Physics

Countering the Threat of Improvised Explosive Devices: Basic Research Opportunities: Abbreviated Version - National Research Council (The National Academies Press, 2007)
Attacks in London, Madrid, Bali, Oklahoma City and other places indicate that improvised explosive devices (IEDs) are among the weapons of choice of terrorists throughout the world. Scientists and engineers have developed various technologies that have been used to counter individual IED attacks, but events in Iraq and elsewhere indicate that the effectiveness of IEDs as weapons of asymmetric warfare remains. The Office of Naval Research has asked The National Research Council to examine the current state of knowledge and practice in the prevention, detection, and mitigation of the effects of IEDs and make recommendations for avenues of research toward the goal of making these devices an ineffective tool of asymmetric warfare. The book includes recommendations such as identifying the most important and most vulnerable elements in the chain of events leading up to an IED attack, determining how resources can be controlled in order to prevent the construction of IEDs, new analytical methods and data modeling to predict the ever-changing behavior of insurgents/terrorists, a deeper understanding of social divisions in societies, enhanced capabilities for persistent surveillance, and improved IED detection capabilities.
Keywords: Conflict and Security Issues

Materials Research to Meet 21st-Century Defense Needs - National Research Council (The National Academies Press, 2003)
In order to achieve the revolutionary new defense capabilities offered by materials science and engineering, innovative management to reduce the risks associated with translating research results will be needed along with the R&D. While payoff is expected to be high from the promising areas of materials research, many of the benefits are likely to be evolutionary. Nevertheless, failure to invest in more speculative areas of research could lead to undesired technological surprises. Basic research in physics, chemistry, biology, and materials science will provide the seeds for potentially revolutionary technologies later in the 21st century.
Keywords: Engineering and Technology; Math, Chemistry, and Physics

The Role of the Chemical Sciences in Finding Alternatives to Critical Resources: A Workshop Summary - National Research Council (The National Academies Press, 2012)
The Chemical Sciences Roundtable (CSR) was established in 1997 by the National Research Council (NRC). It provides a science oriented apolitical forum for leaders in the chemical sciences to discuss chemistry-related issues affecting government, industry, and universities. Organized by the National Research Council's Board on Chemical Sciences and Technology, the CSR aims to strengthen the chemical sciences by fostering communication among the people and organizations - spanning industry, government, universities, and professional associations - involved with the chemical enterprise. One way it does this is by organizing workshops that address issues in chemical science and technology that require national attention. In September 2011, the CSR organized a workshop on the topic, "The Role of Chemical Sciences in Finding Alternatives to Critical Resources." The one-and-a-half-day workshop addressed key topics, including the economic and political matrix, the history of societal responses to key mineral and material shortages, the applications for and properties of existing minerals and materials, and the chemistry of possible replacements. The workshop featured several presentations highlighting the importance of critical nonfuel mineral and material resources in history, catalysis, agriculture, and electronic, magnetic, and optical applications. The Role of the Chemical Sciences in Finding Alternatives to Critical Resources: A Workshop Summary explains the presentations and discussions that took place at the workshop. In accordance with the policies of the NRC, the workshop did not attempt to establish any conclusions or recommendations about needs and future directions, focusing instead on issues identified by the speakers.
Keywords: Math, Chemistry, and Physics; Energy and Energy Conservation

Research Briefings 1987 - National Academy of Sciences; National Academy of Engineering; Institute of Medicine (The National Academies Press, 1988)
Each year since 1982 the Committee on Science, Engineering, and Public Policy has briefed the White House Office of Science and Technology Policy and the National Science Foundation on important progress in U.S. science and technology and major areas of research opportunity. This year the research briefing topics are "Order, Chaos, and Patterns: Aspects of Nonlinearity"; "Biological Control in Managed Ecosystems"; "Chemical Processing of Materials and Devices for Information Storage and Handling"; and "High-Temperature Superconductivity." The 1987 briefings also cover a policy topic, "Research and Research Funding: Impact, Trends, and Policies," a new step toward addressing a wider range of issues in the research briefing format.
Keywords: Policy for Science and Technology

Sustaining Our Water Resources - National Research Council (The National Academies Press, 1993)
This volume, a collection of seven essays by individuals prominent in the water resources field, commemorates the tenth anniversary of the Water Science and Technology Board. The essays cover a variety of current issues in the field, including intergenerational fairness and water resources, the relationship between policy and science for American rivers, changing values and perceptions in the hydrologic sciences, challenges to water resources decision making, and changing concepts of systems management. An overview of institutions in the field is also given.
Keywords: Environment and Environmental Studies

Implementing Health-Protective Features and Practices in Buildings: Workshop Proceedings: Federal Facilities Council Technical Report #148 - National Research Council (The National Academies Press, 2005)
Indoor environmental quality (IEQ) is influenced by building design; heating, ventilation, and air-conditioning systems; and construction materials, as well as by building operations, maintenance, and housekeeping procedures. Increasing evidence suggests that adverse health outcomes in employees, students, hospital patients, and others are linked to the presence of indoor pollutants and other aspects of poor-quality indoor environments. Implementing Health-Protective Features and Practices in Buildings explores this issue and discusses ongoing research and possible strategies for implementing changes in standards and practices for indoor environmental quality.
Keywords: Engineering and Technology; Health and Medicine

CONFERENCE ON HEMOGLOBIN: 2-3 MAY 1957 (The National Academies Press, 1958)
Keywords: Health and Medicine

Exhaust Emissions from In-Use General Aviation Aircraft - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Airport Cooperative Research Program (ACRP) Research Report 164: Exhaust Emissions from In-Use General Aviation Aircraft providesemissions datato better understand and estimate general aviation (GA) aircraft emissions. Aircraft emissions data for smaller aircraft such as piston and small turbine-powered aircraft either do not exist or have not been independently verified. The emissions data obtained as a part of this project can be added to the U.S. Federal Aviation Administration's (FAA’s) Aviation Environmental Design Tool (AEDT) database of aircraft engines. APowerPoint presentationprovides an overview of the findings.Disclaimer: This spreadsheet is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences, Engineering, and Medicine or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Letter Report to Review and Comment on the Phase II Draft Report Prepared for the CDC by the Risk Assessment Corporation (RAC) Titled "Savannah River Site Environmental Dose Reconstruction Project Phase II" - National Research Council (The National Academies Press, 2000)

Global Tropospheric Chemistry: A Plan for Action - National Research Council (The National Academies Press, 1984)
In a giant step toward managing today's pollution problems more effectively, this report lays out a framework to coordinate an interdisciplinary and international investigation of the chemical composition and cycles of the troposphere. The approach includes geographical surveys, field measurements, the development of appropriate models, and improved instrumentation.
Keywords: Environment and Environmental Studies

Opportunities in Chemistry - National Research Council (The National Academies Press, 1985)
Opportunities in Chemistry is based on the contributions of hundreds of American chemists in academia and industry and should be taken as the best available consensus of the chemical community regarding its intellectual frontiers and the economic opportunities that lie beyond them," says Science. This volume addresses the direction in which today's chemical research is heading, including recent developments, technological applications, and the ways advances in chemistry can be used to improve the human condition. In addition, the book examines economic and political implications of chemical research and lists resources for basic research and education in the chemical sciences.
Keywords: Math, Chemistry, and Physics

Science at the Frontier - National Academy of Sciences (The National Academies Press, 1992)
Science at the Frontier takes you on a journey through the minds of some of the nation's leading young scientists as they explore the most exciting areas of discovery today. Based on the second Frontiers of Science symposium sponsored by the National Academy of Sciences, this book describes recent accomplishments and new directions in ten basic fields, represented by outstanding scientists convening to discuss their research. It captures the excitement and personal quality of these exchanges, sometimes pointing to surprising connections spanning the boundaries of traditional disciplines, while providing a context for the reader that explains the basic scientific framework for the fields under discussion. The volume explores: New modifications to scientific theory as geologists probe deep inside the earth and astrophysicists reach to the limits of the observable universe for answers to some of nature's most fundamental and vexing questions. The influence of research in smog formation on the public debate about how to effectively control air pollution. The increasing use of computer modeling in science, from describing the evolution of cellular automata to revealing the workings of the human brain via neural networks. The rise of dynamical systems (the study of chaotic behavior in nature) to a full-fledged science. The search to understand the regulation of gene activity and the many biological problems—such as the onset of cancer—to which it applies. Recent progress in the quest to transform what we know about photosynthesis into functional, efficient systems to tap the sun's energy. Current developments in magnetic resonance imaging and its promise for new breakthroughs in medical diagnosis. Throughout this work the reader is witness to scientific discovery and debate centered on such common concerns as the dramatic and transforming effect of computers on scientists' thinking and research; the development of more cross-disciplinary perspectives; and the very nature of the scientific enterprise itself—what it is to be part of it, and its significance for society. Science at the Frontier is must reading for informed lay readers, scientists interested in fields other than their own, and science students considering a future specialization.
Keywords: Policy for Science and Technology

Connecting Quarks with the Cosmos: Eleven Science Questions for the New Century - National Research Council (The National Academies Press, 2003)
Advances made by physicists in understanding matter, space, and time and by astronomers in understanding the universe as a whole have closely intertwined the question being asked about the universe at its two extremes—the very large and the very small. This report identifies 11 key questions that have a good chance to be answered in the next decade. It urges that a new research strategy be created that brings to bear the techniques of both astronomy and sub-atomic physics in a cross-disciplinary way to address these questions. The report presents seven recommendations to facilitate the necessary research and development coordination. These recommendations identify key priorities for future scientific projects critical for realizing these scientific opportunities.
Keywords: Math, Chemistry, and Physics; Space and Aeronautics

Design Fires in Road Tunnels - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 415: Design Fires in Road Tunnels information on the state of the practice of design fires in road tunnels, focusing on tunnel fire dynamics and the means of fire management for design guidance.Note: On September 20, 2011, the following errata was released related to NCHRP Synthesis 415. The electronic version of the publicaiton was changed to reflect the corrections.On pages 106 and 107, an incorrect reference was cited. In the final paragraph on page 106, the last sentence should read: One study came to the conclusion that, although some minimum water application rates would achieve a certain objective, a marginally higher rate would not necessarily improve the situation (79). The figure caption for Figure 35 at the bottom of page 107 should read: FIGURE 35 NFPA 13, NFPA 15, and other International Water Application Rates (79).The added reference is as follows:79. Harris, K., “Water Application Rates for Fixed Fire Fighting Systems in Road Tunnels,” Proceedings from the Fourth International Symposium on Tunnel Safety and Security, A. Lönnermark and H. Ingason, Eds., Frankfurt am Main, Germany, Mar. 17–19, 2010.
Keywords: Transportation and Infrastructure

The Effects on the Atmosphere of a Major Nuclear Exchange - National Research Council (The National Academies Press, 1985)
Most of the earth's population would survive the immediate horrors of a nuclear holocaust, but what long-term climatological changes would affect their ability to secure food and shelter? This sobering book considers the effects of fine dust from ground-level detonations, of smoke from widespread fires, and of chemicals released into the atmosphere. The authors use mathematical models of atmospheric processes and data from natural situations—e.g., volcanic eruptions and arctic haze—to draw their conclusions. This is the most detailed and comprehensive probe of the scientific evidence published to date.
Keywords: Environment and Environmental Studies

Assessing the Requirements for Sustained Ocean Color Research and Operations - National Research Council (The National Academies Press, 2011)
The ocean is a fundamental component of the earth's biosphere. It covers roughly 70 percent of Earth's surface and plays a pivotal role in the cycling of life's building blocks, such as nitrogen, carbon, oxygen, and sulfur. The ocean also contributes to regulating the climate system. Most of the primary producers in the ocean comprise of microscopic plants and some bacteria; and these photosynthetic organisms (phytoplankton) form the base of the ocean's food web. Monitoring the health of the ocean and its productivity is critical to understanding and managing the ocean's essential functions and living resources. Because the ocean is so vast and difficult for humans to explore, satellite remote sensing of ocean color is currently the only way to observe and monitor the biological state of the surface ocean globally on time scales of days to decades. Ocean color measurements reveal a wealth of ecologically important characteristics including: chlorophyll concentration, the rate of phytoplankton photosynthesis, sediment transport, dispersion of pollutants, and responses of oceanic biota to long-term climate changes. Continuity of satellite ocean color data and associated climate research products are presently at significant risk for the U.S. ocean color community. Assessing Requirements for Sustained Ocean Color Research and Operations aims to identify the ocean color data needs for a broad range of end users, develop a consensus for the minimum requirements, and outline options to meet these needs on a sustained basis. The report assesses lessons learned in global ocean color remote sensing from the SeaWiFS/MODIS era to guide planning for acquisition of future global ocean color radiance data to support U.S. research and operational needs.
Keywords: Earth Sciences

Preservation of Historical Records - National Research Council (The National Academies Press, 1986)
With discussion on how paper conservation procedures work, how they are put to use, and how deterioration may be prevented, this comprehensive volume examines how vast quantities of documentation can best be preserved. It provides detailed information and recommendations about various preservation methods, including mechanical copying, photographic film, magnetic recording, and optical disk recording, and on the expected useful lives of each. Also included are a method for scoring and assessing the condition of collections and a decision tree that provides a guide for orderly progress in preserving a collection of documents. Printed on permanent, acid-free paper.
Keywords: Engineering and Technology

Oceanography and Naval Special Warfare: Opportunities and Challenges - National Research Council (The National Academies Press, 1997)
Missions by Sea, Air, and Land (SEAL) teams and other naval units involved in Naval Special Warfare encompass some of the most unique and arduous challenges facing naval personnel in combat situations. Real-time decision- making is crucial, and the need for adequate and accurate environmental data is paramount for minimizing uncertainty, reducing risk, and ensuring mission success. Based on discussions among more than 100 scientists, managers, and warfighters during the fifth in a series of symposia, this book summarizes the SEAL teams' mission and methods, the importance of environmental data in planning and executing naval special operations, and ways to expand the Navy's ability to support this elite group of warfighters. (Color photographs and satellite imagery)
Keywords: Conflict and Security Issues; Earth Sciences

Review of the NARSTO Draft Report: NARSTO Assessment of the Atmospheric Science on Particulate Matter - National Research Council (The National Academies Press, 2002)
Keywords: Environment and Environmental Studies

Issues in the Integration of Research and Operational Satellite Systems for Climate Research: Part I. Science and Design - National Research Council (The National Academies Press, 2000)
Currently, the Departments of Defense (DOD) and Commerce (DOC) acquire and operate separate polarorbiting environmental satellite systems that collect data needed for military and civil weather forecasting. The National Performance Review (NPR) and subsequent Presidential Decision Directive (PDD), directed the DOD (Air Force) and the DOC (National Oceanic and Atmospheric Administration, NOAA) to establish a converged national weather satellite program that would meet U.S. civil and national security requirements and fulfill international obligations. NASA's Earth Observing System (EOS), and potentially other NASA programs, were included in the converged program to provide new remote sensing and spacecraft technologies that could improve the operational capabilities of the converged system. The program that followed, called the National Polar-orbiting Operational Environmental Satellite System (NPOESS), combined the follow-on to the DOD's Defense Meteorological Satellite Program and the DOC's Polar-orbiting Operational Environmental Satellite (POES) program. The tri-agency Integrated Program Office (IPO) for NPOESS was subsequently established to manage the acquisition and operations of the converged satellite. Issues in the Integration of Research and Operational Satellite Systems for Climate Research analyzes issues related to the integration of EOS and NPOESS, especially as they affect research and monitoring activities related to Earth's climate and whether it is changing.
Keywords: Earth Sciences; Space and Aeronautics

(NAS Colloquium) Vision: From Photon to Perception (The National Academies Press, 1999)
Keywords: Biology and Life Sciences

Review of the Department of Energy's Inertial Confinement Fusion Program (The National Academies Press, 1986)
Keywords: Energy and Energy Conservation

Sensor Systems for Biological Agent Attacks: Protecting Buildings and Military Bases - National Research Council (The National Academies Press, 2005)
Over the last ten years, there has been growing concern about potential biological attacks on the nation’s population and its military facilities. It is now possible to detect such attacks quickly enough to permit treatment of potential victims prior to the onset of symptoms. The capability to “detect to warn”, that is in time to take action to minimize human exposure, however, is still lacking. To help achieve such a capability, the Defense Threat Reduction Agency (DTRA) asked the National Research Council (NRC) to assess the development path for “detect to warn” sensors systems. This report presents the results of this assessment including analysis of scenarios for protecting facilities, sensor requirements, and detection technologies and systems. Findings and recommendations are provided for the most probable path to achieve a detect-to-warn capability and potential technological breakthroughs that could accelerate its attainment.
Keywords: Conflict and Security Issues; Health and Medicine

An Assessment of the Divisions of the Physical Measurement Laboratory at the National Institute of Standards and Technology Located in Boulder, Colorado: Fiscal Year 2023 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Since 1959, the National Institute of Standards and Technology (NIST) has annually commissioned the National Academies of Sciences, Engineering, and Medicine to assess its various measurements and standards laboratories. This report appraises the Physical Measurement Laboratory (PML), assessing four divisions of PML situated at the NIST Boulder campus: the Applied Physics Division, the Time and Frequency Division, the Quantum Electromagnetics Division, and the Quantum Physics Division. The report compares the caliber of research at PML with similar international programs to determine whether programs adequately align with its objectives; assesses the range of scientific and technical expertise available within PML; considers the budget, facilities, equipment, and Human Resources to bolster PML technical endeavors and contribute to the fulfillment of its goals; and assesses the efficacy of PML methods for disseminating the products of its work.
Keywords: Engineering and Technology

Beyond the Molecular Frontier: Challenges for Chemistry and Chemical Engineering - National Research Council (The National Academies Press, 2003)
Chemistry and chemical engineering have changed significantly in the last decade. They have broadened their scope—into biology, nanotechnology, materials science, computation, and advanced methods of process systems engineering and control—so much that the programs in most chemistry and chemical engineering departments now barely resemble the classical notion of chemistry. Beyond the Molecular Frontier brings together research, discovery, and invention across the entire spectrum of the chemical sciences—from fundamental, molecular-level chemistry to large-scale chemical processing technology. This reflects the way the field has evolved, the synergy at universities between research and education in chemistry and chemical engineering, and the way chemists and chemical engineers work together in industry. The astonishing developments in science and engineering during the 20th century have made it possible to dream of new goals that might previously have been considered unthinkable. This book identifies the key opportunities and challenges for the chemical sciences, from basic research to societal needs and from terrorism defense to environmental protection, and it looks at the ways in which chemists and chemical engineers can work together to contribute to an improved future.
Keywords: Math, Chemistry, and Physics; Computers and Information Technology

BIO2010: Transforming Undergraduate Education for Future Research Biologists - National Research Council (The National Academies Press, 2003)
Biological sciences have been revolutionized, not only in the way research is conducted—with the introduction of techniques such as recombinant DNA and digital technology—but also in how research findings are communicated among professionals and to the public. Yet, the undergraduate programs that train biology researchers remain much the same as they were before these fundamental changes came on the scene. This new volume provides a blueprint for bringing undergraduate biology education up to the speed of today's research fast track. It includes recommendations for teaching the next generation of life science investigators, through: Building a strong interdisciplinary curriculum that includes physical science, information technology, and mathematics. Eliminating the administrative and financial barriers to cross-departmental collaboration. Evaluating the impact of medical college admissions testing on undergraduate biology education. Creating early opportunities for independent research. Designing meaningful laboratory experiences into the curriculum. The committee presents a dozen brief case studies of exemplary programs at leading institutions and lists many resources for biology educators. This volume will be important to biology faculty, administrators, practitioners, professional societies, research and education funders, and the biotechnology industry.
Keywords: Education

Neutrino Astrophysics: A Research Briefing (The National Academies Press, 1995)
Keywords: Space and Aeronautics

Aspects of Weather and Space Weather in the Earth's Upper Atmosphere: The Role of Internal Atmospheric Waves - Michael C. Kelley (The National Academies Press, 1997)
Keywords: Earth Sciences; Space and Aeronautics

Opportunities in Biology - National Research Council (The National Academies Press, 1989)
Biology has entered an era in which interdisciplinary cooperation is at an all-time high, practical applications follow basic discoveries more quickly than ever before, and new technologies—recombinant DNA, scanning tunneling microscopes, and more—are revolutionizing the way science is conducted. The potential for scientific breakthroughs with significant implications for society has never been greater. Opportunities in Biology reports on the state of the new biology, taking a detailed look at the disciplines of biology; examining the advances made in medicine, agriculture, and other fields; and pointing out promising research opportunities. Authored by an expert panel representing a variety of viewpoints, this volume also offers recommendations on how to meet the infrastructure needs—for funding, effective information systems, and other support—of future biology research. Exploring what has been accomplished and what is on the horizon, Opportunities in Biology is an indispensable resource for students, teachers, and researchers in all subdisciplines of biology as well as for research administrators and those in funding agencies.
Keywords: Biology and Life Sciences

Fire Research Abstracts and Reviews, Volume 13 - National Research Council (The National Academies Press, 1971)
Keywords: Engineering and Technology

Fire Research Abstracts and Reviews, Volume 18 - National Research Council (The National Academies Press, 1976)
Keywords: Engineering and Technology

2015-2016 Assessment of the Army Research Laboratory: Interim Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The National Academies of Sciences, Engineering, and Medicine's Army Research Laboratory Technical Assessment Board (ARLTAB) provides biennial assessments of the scientific and technical quality of the research, development, and analysis programs at the Army Research Laboratory (ARL), focusing on ballistics sciences, human sciences, information sciences, materials sciences, and mechanical sciences. This interim report summarizes the findings of the Board for the first year of this biennial assessment; the current report addresses approximately half the portfolio for each campaign; the remainder will be assessed in 2016. During the first year the Board examined the following elements within the ARL's science and technology campaigns: biological and bioinspired materials, energy and power materials, and engineered photonics materials; battlefield injury mechanisms, directed energy, and armor and adaptive protection; sensing and effecting, and system intelligence and intelligent systems; advanced computing architectures, computing sciences, data-intensive sciences, and predictive simulation sciences; human-machine interaction, intelligence and control, and perception; humans in multiagent systems, real-world behavior, and toward human variability; and mission capability of systems. A second, final report will subsume the findings of this interim report and add the findings from the second year of the review.
Keywords: Conflict and Security Issues

Protecting Building Occupants and Operations from Biological and Chemical Airborne Threats: A Framework for Decision Making - National Research Council (The National Academies Press, 2007)
Protecting buildings and their occupants from biological and chemical attacks to ensure continuous building operations is seen as an urgent need in the Department of Defense, given recent technological advances and the changing threats. Toward this end, the Department of Defense established the Immune Building Program to develop protective systems to deter biological and chemical attacks on military facilities and minimize the impacts of attacks should they occur. At the request of the Defense Threat Reduction Agency, the National Research Council convened a committee to provide guiding principles for protecting buildings from airborne biological or chemical threat agents and outline the variables and options to consider in designing building protection systems. This report addresses such components of building protection as building design and planning strategies; heating, ventilating, and air-conditioning systems; filtration; threat detection and identification technologies; and operational responses. It recommends that building protection systems be designed to accommodate changing building conditions, new technologies, and emerging threats. Although the report's focus is on protection of military facilities, the guiding principles it offers are applicable to protection of public facilities as well.
Keywords: Engineering and Technology; Environment and Environmental Studies

2011-2012 Assessment of the Army Research Laboratory - National Research Council (The National Academies Press, 2013)
The charge of the Army Research Laboratory Technical Assessment Board (ARLTAB) is to provide biennial assessments of the scientific and technical quality of the research, development, and analysis programs at the Army Research Laboratory (ARL). The ARLTAB is assisted by six panels, each of which focuses on the portion of the ARL program conducted by one of ARL's six directorates1. When requested to do so by ARL, the ARLTAB also examines work that cuts across the directorates. For example, during 2011-2012, ARL requested that the ARLTAB examine crosscutting work in the areas of autonomous systems and network science. The overall quality of ARL's technical staff and their work continues to be impressive. Staff continue to demonstrate clear, passionate mindfulness of the importance of transitioning technology to support immediate and longer-term Army needs. Their involvement with the wider scientific and engineering community continues to expand. Such continued involvement and collaboration are fundamentally important for ARL's scientific and technical activities and need to include the essential elements of peer review and interaction through publications and travel to attend professional meetings, including international professional meetings. In general, ARL is working very well within an appropriate research and development niche and has been demonstrating significant accomplishments, as exemplified in the following discussion, which also addresses opportunities and challenges.
Keywords: Conflict and Security Issues

Assessment of the In-House Laboratory Independent Research at the Army's Research, Development, and Engineering Centers - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
This report evaluates the In-House Laboratory Independent Research (ILIR) conducted at the Research, Development, and Engineering Centers (RDECs) of the U.S. Army’s Research, Development, and Engineering Command (RDECOM) during 2018. It reviews and offers recommendations for each of the eight areas of ILIR research: chemistry, computational sciences, electronics, life sciences, materials science, mechanical sciences, network sciences, and physics.
Keywords: Conflict and Security Issues; Policy for Science and Technology

Indoor Exposure to Fine Particulate Matter and Practical Mitigation Approaches: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine; National Academy of Engineering (The National Academies Press, 2022)
Overwhelming evidence exists that exposure to outdoor fine particulate matter (PM2.5) is associated with a range of short-term and chronic health impacts, including asthma exacerbation, acute and chronic bronchitis, heart attacks, increased susceptibility to respiratory infections, and premature death, with the burden of these health effects falling more heavily on underserved and marginalized communities. Although less studied to date, indoor exposure to PM2.5 is also gaining attention as a potential source of adverse health effects, particularly given that Americans spend 90 percent of their lives indoors and indoor PM2.5 levels can exceed outdoor levels. To better understand the sources of indoor PM2.5, the possible health effects of exposure to indoor PM2.5, and engineering approaches and interventions to reduce those exposure risks, the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop, Indoor Exposure to Fine Particulate Matter and Practical Mitigation Approaches, on April 14, 21, and 28, 2021. The workshop focused on exposures that occur in residential and school buildings and on existing and practical mitigation technologies and approaches. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Fire Research Abstracts and Reviews, Volume 6 - National Research Council (The National Academies Press, 1964)
Keywords: Engineering and Technology

New Pathways in Science and Technology: Collected Research Briefings, 1982-1984 - National Academy of Engineering; Institute of Medicine (The National Academies Press, 1985)
Keywords: Policy for Science and Technology

Causes and Effects of Stratospheric Ozone Reduction: An Update - National Research Council (The National Academies Press, 1982)
Keywords: Environment and Environmental Studies

Nanophotonics: Accessibility and Applicability - National Research Council (The National Academies Press, 2008)
The Committee on Technology Insight-Gauge, Evaluate & Review set up by the NRC at the request of the Defense Intelligence Agency, has selected a number of emerging technologies to investigate for their potential threats to and opportunities for national security. This first study focused on emerging applications of nanophotonics, which is about the interaction of matter and light at the scale of the wavelength of the light. Manipulation of matter at that scale allows tailoring the optical properties to permit a wide-range of commercial and defense applications. This book presents a review of the nanoscale phenomena underpinning nanophotonics, an assessment of enabling technologies for developing new applications, an examination of potential military applications, and an assessment of foreign investment capabilities
Keywords: Conflict and Security Issues; Engineering and Technology

Global Sources of Local Pollution: An Assessment of Long-Range Transport of Key Air Pollutants to and from the United States - National Research Council (The National Academies Press, 2010)
Recent advances in air pollution monitoring and modeling capabilities have made it possible to show that air pollution can be transported long distances and that adverse impacts of emitted pollutants cannot be confined to one country or even one continent. Pollutants from traffic, cooking stoves, and factories emitted half a world away can make the air we inhale today more hazardous for our health. The relative importance of this "imported" pollution is likely to increase, as emissions in developing countries grow, and air quality standards in industrial countries are tightened. Global Sources of Local Pollution examines the impact of the long-range transport of four key air pollutants (ozone, particulate matter, mercury, and persistent organic pollutants) on air quality and pollutant deposition in the United States. It also explores the environmental impacts of U.S. emissions on other parts of the world. The book recommends that the United States work with the international community to develop an integrated system for determining pollution sources and impacts and to design effective response strategies. This book will be useful to international, federal, state, and local policy makers responsible for understanding and managing air pollution and its impacts on human health and well-being.
Keywords: Environment and Environmental Studies

Strategies to Protect the Health of Deployed U.S. Forces: Detecting, Characterizing, and Documenting Exposures - National Research Council (The National Academies Press, 2000)
Since Operation Desert Shield/Desert Storm, Gulf War veterans have expressed concerns about health effects that could be associated with their deployment and service during the war. Although similar concerns were raised after other military operations, the Gulf War deployment focused national attention on the potential, but uncertain, relationship between the presence of chemical and biological (CB) agents and other harmful agents in theater and health symptoms reported by military personnel. Strategies to Protect the Health of Deployed U.S. Forces which is one of the four two-year studies, examines the detection and tracking of exposures of deployed personnel to multiple harmful agents.
Keywords: Health and Medicine; Environment and Environmental Studies; Conflict and Security Issues

Alternative Applications of Atomic Vapor Laser Isotope Separation Technology (The National Academies Press, 1991)
Keywords: Engineering and Technology

Doctorates Conferred in the Sciences by American Universities 1931-1932: Reprint and Circular Series of the National Research Council (The National Academies Press, 1932)
Keywords: Math, Chemistry, and Physics

Frontiers of Materials Research: A Decadal Survey - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Modern materials science builds on knowledge from physics, chemistry, biology, mathematics, computer and data science, and engineering sciences to enable us to understand, control, and expand the material world. Although it is anchored in inquiry-based fundamental science, materials research is strongly focused on discovering and producing reliable and economically viable materials, from super alloys to polymer composites, that are used in a vast array of products essential to today's societies and economies. Frontiers of Materials Research: A Decadal Survey is aimed at documenting the status and promising future directions of materials research in the United States in the context of similar efforts worldwide. This third decadal survey in materials research reviews the progress and achievements in materials research and changes in the materials research landscape over the last decade; research opportunities for investment for the period 2020-2030; impacts that materials research has had and is expected to have on emerging technologies, national needs, and science; and challenges the enterprise may face over the next decade.
Keywords: Engineering and Technology

Detection and Measurement of Nuclear Radiation - National Research Council (The National Academies Press, 1962)
Keywords: Math, Chemistry, and Physics

Laser Radar: Progress and Opportunities in Active Electro-Optical Sensing - National Research Council (The National Academies Press, 2014)
In today's world, the range of technologies with the potential to threaten the security of U.S. military forces is extremely broad. These include developments in explosive materials, sensors, control systems, robotics, satellite systems, and computing power, to name just a few. Such technologies have not only enhanced the capabilities of U.S. military forces, but also offer enhanced offensive capabilities to potential adversaries - either directly through the development of more sophisticated weapons, or more indirectly through opportunities for interrupting the function of defensive U.S. military systems. Passive and active electro-optical (EO) sensing technologies are prime examples. Laser Radar considers the potential of active EO technologies to create surprise; i.e., systems that use a source of visible or infrared light to interrogate a target in combination with sensitive detectors and processors to analyze the returned light. The addition of an interrogating light source to the system adds rich new phenomenologies that enable new capabilities to be explored. This report evaluates the fundamental, physical limits to active EO sensor technologies with potential military utility; identifies key technologies that may help overcome the impediments within a 5-10 year timeframe; considers the pros and cons of implementing each existing or emerging technology; and evaluates the potential uses of active EO sensing technologies, including 3D mapping and multi-discriminate laser radar technologies.
Keywords: Conflict and Security Issues

Evaluating Vehicle Emissions Inspection and Maintenance Programs - Transportation Research Board; National Research Council (The National Academies Press, 2001)
Emissions inspection and maintenance (I/M) programs subject vehicles to periodic inspections of their emission control systems. Despite widespread use of these programs in air-quality management, policy makers and the public have found a number of problems associated with them. Prominent among these issues is the perception that emissions benefits and other impacts of I/M programs have not been evaluated adequately. Evaluating Vehicle Emissions Inspection and Maintenance Programs assesses the effectiveness of these programs for reducing mobile source emissions. In this report, the committee evaluates the differences in the characteristics of motor vehicle emissions in areas with and without I/M programs, identifies criteria and methodologies for their evaluation, and recommends improvements to the programs. Most useful of all, this book will help summarize the observed benefits of these programs and how they can be redirected in the future to increase their effectiveness.
Keywords: Environment and Environmental Studies; Transportation and Infrastructure

Condensed-Matter and Materials Physics: Basic Research for Tomorrow's Technology - National Research Council (The National Academies Press, 1999)
This book identifies opportunities, priorities, and challenges for the field of condensed-matter and materials physics. It highlights exciting recent scientific and technological developments and their societal impact and identifies outstanding questions for future research. Topics range from the science of modern technology to new materials and structures, novel quantum phenomena, nonequilibrium physics, soft condensed matter, and new experimental and computational tools. The book also addresses structural challenges for the field, including nurturing its intellectual vitality, maintaining a healthy mixture of large and small research facilities, improving the field's integration with other disciplines, and developing new ways for scientists in academia, government laboratories, and industry to work together. It will be of interest to scientists, educators, students, and policymakers.
Keywords: Engineering and Technology; Math, Chemistry, and Physics

Frontiers in Chemical Engineering: Research Needs and Opportunities - National Research Council (The National Academies Press, 1988)
In the next 10 to 15 years, chemical engineers have the potential to affect every aspect of American life and promote the scientific and industrial leadership of the United States. Frontiers in Chemical Engineering explores the opportunities available and gives a blueprint for turning a multitude of promising visions into realities. It also examines the likely changes in how chemical engineers will be educated and take their place in the profession, and presents new research opportunities.
Keywords: Math, Chemistry, and Physics

Physics of Life - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Biological physics, or the physics of living systems, has emerged fully as a field of physics, alongside more traditional fields of astrophysics and cosmology, atomic, molecular and optical physics, condensed matter physics, nuclear physics, particle physics, and plasma physics. This new field brings the physicist's style of inquiry to bear on the beautiful phenomena of life. The enormous range of phenomena encountered in living systems - phenomena that often have no analog or precedent in the inanimate world - means that the intellectual agenda of biological physics is exceptionally broad, even by the ambitious standards of physics. Physics of Life is the first decadal survey of this field, as part of a broader decadal survey of physics. This report communicates the importance of biological physics research; addresses what must be done to realize the promise of this new field; and provides guidance for informed decisions about funding, workforce, and research directions.
Keywords: Math, Chemistry, and Physics; Biology and Life Sciences

Mathematics and Physics of Emerging Biomedical Imaging - National Research Council (The National Academies Press, 1996)
This cross-disciplinary book documents the key research challenges in the mathematical sciences and physics that could enable the economical development of novel biomedical imaging devices. It is hoped that the infusion of new insights from mathematical scientists and physicists will accelerate progress in imaging. Incorporating input from dozens of biomedical researchers who described what they perceived as key open problems of imaging that are amenable to attack by mathematical scientists and physicists, this book introduces the frontiers of biomedical imaging, especially the imaging of dynamic physiological functions, to the educated nonspecialist. Ten imaging modalities are covered, from the well-established (e.g., CAT scanning, MRI) to the more speculative (e.g., electrical and magnetic source imaging). For each modality, mathematics and physics research challenges are identified and a short list of suggested reading offered. Two additional chapters offer visions of the next generation of surgical and interventional techniques and of image processing. A final chapter provides an overview of mathematical issues that cut across the various modalities.
Keywords: Math, Chemistry, and Physics; Engineering and Technology; Surveys and Statistics

Globalization of Technology: International Perspectives - Janet H. Muroyama; H. Guyford (The National Academies Press, 1988)
The technological revolution has reached around the world, with important consequences for business, government, and the labor market. Computer-aided design, telecommunications, and other developments are allowing small players to compete with traditional giants in manufacturing and other fields. In this volume, 16 engineering and industrial experts representing eight countries discuss the growth of technological advances and their impact on specific industries and regions of the world. From various perspectives, these distinguished commentators describe the practical aspects of technology's reach into business and trade.
Keywords: Industry and Labor

Biographical Memoirs: Volume 57 - National Academy of Sciences (The National Academies Press, 1987)
This distinguished series contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. A cumulative index for all 57 volumes is now included. For historical and bibliographical purposes, these volumes are worth returning to time and again. Volume 57 includes biographies of: Arthur Francis Buddington, J. George Harrar, Paul Herget, John Dove Isaacs III, Bessel Kok, Otto Krayer, Rebecca Craighill Lancefield, Harold Dwight Lasswell, Jay Laurence Lush, John Howard Mueller, Robert Franklin Pitts, John Robert Raper, Karl Sax, Gerhard Schmidt, Leslie Spier, Hans-Lukas Teuber, and Warren Weaver.
Keywords: Biography and Autobiography

Global Environmental Change: Research Pathways for the Next Decade - National Research Council (The National Academies Press, 1999)
How can we understand and rise to the environmental challenges of global change? One clear answer is to understand the science of global change, not solely in terms of the processes that control changes in climate and the composition of the atmosphere, but in how ecosystems and human society interact with these changes. In the last two decades of the twentieth century, a number of such research efforts—supported by computer and satellite technology—have been launched. Yet many opportunities for integration remain unexploited, and many fundamental questions remain about the earth's capacity to support a growing human population. This volume encourages a renewed commitment to understanding global change and sets a direction for research in the decade ahead. Through case studies the book explores what can be learned from the lessons of the past 20 years and what are the outstanding scientific questions. Highlights include: Research imperatives and strategies for investigators in the areas of atmospheric chemistry, climate, ecosystem studies, and human dimensions of global change. The context of climate change, including lessons to be gleaned from paleoclimatology. Human responses to—and forcing of—projected global change. This book offers a comprehensive overview of global change research to date and provides a framework for answering urgent questions.
Keywords: Environment and Environmental Studies; Earth Sciences

Opportunities in Biotechnology for Future Army Applications - National Research Council (The National Academies Press, 2001)
This report surveys opportunities for future Army applications in biotechnology, including sensors, electronics and computers, materials, logistics, and medical therapeutics, by matching commercial trends and developments with enduring Army requirements. Several biotechnology areas are identified as important for the Army to exploit, either by direct funding of research or by indirect influence of commercial sources, to achieve significant gains in combat effectiveness before 2025.
Keywords: Biology and Life Sciences; Conflict and Security Issues

Harnessing Light: Optical Science and Engineering for the 21st Century - National Research Council (The National Academies Press, 1998)
Optical science and engineering affect almost every aspect of our lives. Millions of miles of optical fiber carry voice and data signals around the world. Lasers are used in surgery of the retina, kidneys, and heart. New high-efficiency light sources promise dramatic reductions in electricity consumption. Night-vision equipment and satellite surveillance are changing how wars are fought. Industry uses optical methods in everything from the production of computer chips to the construction of tunnels. Harnessing Light surveys this multitude of applications, as well as the status of the optics industry and of research and education in optics, and identifies actions that could enhance the field's contributions to society and facilitate its continued technical development.
Keywords: Engineering and Technology

An Assessment of the National Institute of Standards and Technology Physical Measurement Laboratory: Fiscal Year 2015 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Physical Measurement Laboratory (PML) at the National Institute of Standards and Technology (NIST) is dedicated to three fundamental and complementary tasks: (1) increase the accuracy of our knowledge of the physical parameters that are the foundation of our technology-driven society; (2) disseminate technologies by which these physical parameters can be accessed in a standardized way by the stakeholders; and (3) conduct research at both fundamental and applied levels to provide knowledge that may eventually lead to advances in measurement approaches and standards. This report assesses the scientific and technical work performed by the PML and identifies salient examples of accomplishments, challenges, and opportunities for improvement for each of its nine divisions.
Keywords: Engineering and Technology

Finding Hazardous Asteroids Using Infrared and Visible Wavelength Telescopes - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Near Earth objects (NEOs) have the potential to cause significant damage on Earth. In December 2018, an asteroid exploded in the upper atmosphere over the Bering Sea (western Pacific Ocean) with the explosive force of nearly 10 times that of the Hiroshima bomb. While the frequency of NEO impacts rises in inverse proportion to their sizes, it is still critical to monitor NEO activity in order to prepare defenses for these rare but dangerous threats. Currently, NASA funds a network of ground-based telescopes and a single, soon-to-expire space-based asset to detect and track large asteroids that could cause major damage if they struck Earth. This asset is crucial to NEO tracking as thermal-infrared detection and tracking of asteroids can only be accomplished on a space-based platform. Finding Hazardous Asteroids Using Infrared and Visible Wavelength Telescopes explores the advantages and disadvantages of infrared (IR) technology and visible wavelength observations of NEOs. This report reviews the techniques that could be used to obtain NEO sizes from an infrared spectrum and delineate the associated errors in determining the size. It also evaluates the strengths and weaknesses of these techniques and recommends the most valid techniques that give reproducible results with quantifiable errors.
Keywords: Space and Aeronautics

Critical Technologies: The Role of Chemistry and Chemical Engineering (The National Academies Press, 1992)

Mammography and Beyond: Developing Technologies for the Early Detection of Breast Cancer - Institute of Medicine; National Research Council (The National Academies Press, 2001)
Each year more than 180,000 new cases of breast cancer are diagnosed in women in the U.S. If cancer is detected when small and local, treatment options are less dangerous, intrusive, and costly-and more likely to lead to a cure. Yet those simple facts belie the complexity of developing and disseminating acceptable techniques for breast cancer diagnosis. Even the most exciting new technologies remain clouded with uncertainty. Mammography and Beyond provides a comprehensive and up-to-date perspective on the state of breast cancer screening and diagnosis and recommends steps for developing the most reliable breast cancer detection methods possible. This book reviews the dramatic expansion of breast cancer awareness and screening, examining the capabilities and limitations of current and emerging technologies for breast cancer detection and their effectiveness at actually reducing deaths. The committee discusses issues including national policy toward breast cancer detection, roles of public and private agencies, problems in determining the success of a technique, availability of detection methods to specific populations of women, women's experience during the detection process, cost-benefit analyses, and more. Examining current practices and specifying research and other needs, Mammography and Beyond will be an indispensable resource to policy makers, public health officials, medical practitioners, researchers, women's health advocates, and concerned women and their families.
Keywords: Health and Medicine

Improved Fire- and Smoke-Resistant Materials for Commercial Aircraft Interiors: A Proceedings - National Research Council (The National Academies Press, 1995)
This book describes the Conference on Fire and Smoke-Resistant Materials held at the National Academy of Sciences on November 8-10, 1994. The purpose of this conference was to identify trends in aircraft fire safety and promising research directions for the Federal Aviation Administration's program in smoke and fire resistant materials. This proceedings contains 15 papers presented by distinguished speakers and summaries of the workshop sessions concerning toxicity issues, fire performance parameters, drivers for materials development, and new materials technology.
Keywords: Space and Aeronautics; Environment and Environmental Studies

National Science Education Standards - National Research Council (The National Academies Press, 1996)
Americans agree that our students urgently need better science education. But what should they be expected to know and be able to do? Can the same expectations be applied across our diverse society? These and other fundamental issues are addressed in National Science Education Standards—a landmark development effort that reflects the contributions of thousands of teachers, scientists, science educators, and other experts across the country. The National Science Education Standards offer a coherent vision of what it means to be scientifically literate, describing what all students regardless of background or circumstance should understand and be able to do at different grade levels in various science categories. The standards address: The exemplary practice of science teaching that provides students with experiences that enable them to achieve scientific literacy. Criteria for assessing and analyzing students' attainments in science and the learning opportunities that school science programs afford. The nature and design of the school and district science program. The support and resources needed for students to learn science. These standards reflect the principles that learning science is an inquiry-based process, that science in schools should reflect the intellectual traditions of contemporary science, and that all Americans have a role in improving science education. This document will be invaluable to education policymakers, school system administrators, teacher educators, individual teachers, and concerned parents.
Keywords: Education

Visualizing Chemistry: The Progress and Promise of Advanced Chemical Imaging - National Research Council (The National Academies Press, 2006)
Scientists and engineers have long relied on the power of imaging techniques to help see objects invisible to the naked eye, and thus, to advance scientific knowledge. These experts are constantly pushing the limits of technology in pursuit of chemical imaging—the ability to visualize molecular structures and chemical composition in time and space as actual events unfold—from the smallest dimension of a biological system to the widest expanse of a distant galaxy. Chemical imaging has a variety of applications for almost every facet of our daily lives, ranging from medical diagnosis and treatment to the study and design of material properties in new products. In addition to highlighting advances in chemical imaging that could have the greatest impact on critical problems in science and technology, Visualizing Chemistry reviews the current state of chemical imaging technology, identifies promising future developments and their applications, and suggests a research and educational agenda to enable breakthrough improvements.
Keywords: Math, Chemistry, and Physics; Surveys and Statistics

Issues in Potable Reuse: The Viability of Augmenting Drinking Water Supplies with Reclaimed Water - National Research Council (The National Academies Press, 1998)
A small but growing number of municipalities are augmenting their drinking water supplies with highly treated wastewater. But some professionals in the field argue that only the purest sources should be used for drinking water. Is potable reuse a viable application of reclaimed water? How can individual communities effectively evaluate potable reuse programs? How certain must "certain" be when it comes to drinking water safety? Issues in Potable Reuse provides the best available answers to these questions. Useful to scientists yet accessible to concerned lay readers, this book defines important terms in the debate and provides data, analysis, and examples of the experience of municipalities from San Diego to Tampa. The committee explores in detail the two major types of contaminants: Chemical contaminants. The committee discusses how to assess toxicity, reduce the input of contaminants, evaluate treatment options, manage the byproducts of disinfection and other issues. Microbial contaminants, including newly emerging waterborne pathogens. The book covers methods of detection, health consequences, treatment, and more. Issues in Potable Reuse reviews the results of six health effects studies at operational or proposed reuse projects. The committee discusses the utility of fish versus mammals in toxicology testing and covers issues in quality assurance.
Keywords: Environment and Environmental Studies; Earth Sciences

Chemical and Biological Terrorism: Research and Development to Improve Civilian Medical Response - Institute of Medicine (The National Academies Press, 1999)
The threat of domestic terrorism today looms larger than ever. Bombings at the World Trade Center and Oklahoma City's Federal Building, as well as nerve gas attacks in Japan, have made it tragically obvious that American civilians must be ready for terrorist attacks. What do we need to know to help emergency and medical personnel prepare for these attacks? Chemical and Biological Terrorism identifies the R&D efforts needed to implement recommendations in key areas: pre-incident intelligence, detection and identification of chemical and biological agents, protective clothing and equipment, early recognition that a population has been covertly exposed to a pathogen, mass casualty decontamination and triage, use of vaccines and pharmaceuticals, and the psychological effects of terror. Specific objectives for computer software development are also identified. The book addresses the differences between a biological and chemical attack, the distinct challenges to the military and civilian medical communities, and other broader issues. This book will be of critical interest to anyone involved in civilian preparedness for terrorist attack: planners, administrators, responders, medical professionals, public health and emergency personnel, and technology designers and engineers.
Keywords: Conflict and Security Issues

Film Badge Dosimetry in Atmospheric Nuclear Tests - National Research Council (The National Academies Press, 1989)
During the 18-year program of atmospheric testing of nuclear weapons (1945-1962), some of the 225,000 participants were exposed to radiation. Many of these participants have been experiencing sicknesses that may be test-related. Currently, test participants who had served in military units have pending over 6,000 claims for compensation at the Department of Veterans Affairs. This study presents improved methods for calculating the radiation doses to which these individuals were exposed, and are intended to be useful in the adjudication of their claims.
Keywords: Environment and Environmental Studies

(NAS Colloquium) Computational Biomolecular Science (The National Academies Press, 1998)
Keywords: Biology and Life Sciences

Biographical Memoirs: Volume 51 - National Academy of Sciences (The National Academies Press, 1980)
Biographic Memoirs: Volume 51 contains the biographies of deceased members of the National Academy of Sciences and bibliographies of their published works. Each biographical essay was written by a member of the Academy familiar with the professional career of the deceased. For historical and bibliographical purposes, these volumes are worth returning to time and again.
Keywords: Biography and Autobiography

Scientific Examination of Art: Modern Techniques in Conservation and Analysis (The National Academies Press, 2005)
In March 2003, the National Academy of Sciences Arthur M. Sackler Colloquia presented the Scientific Examination of Art: Modern Techniques in Conservation and Analysis at the National Academy of Sciences Building in Washington, DC. Featuring senior investigators of specific methods and materials, the papers in this book examine the application of scientific methods to the study and conservation of art and cultural properties. The Arthur M. Sackler Colloquia of the National Academy of Sciences address scientific topics of broad and current interest, cutting across the boundaries of traditional disciplines and attracting up to 250 leading researchers in the field. These colloquia are made possible by a generous gift from Mrs. Jill Sackler, in memory of her husband, Arthur M. Sackler. For more information about the Sackler Colloquia, visit www.nasonline.org/sackler
Keywords: Engineering and Technology